Enhancing Cultural Competence in ELT: The Integration of Google Sites and Case Based - Rika, Rika; Saragih, Anggraini T; Erlita, Yeni; Haswani, Fahri (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2024)
The study aims to measure the use of digital media on Google sites which is integrated with case method in English culture in ELT course. It is qualitative research which elaborates the use of digital media Google Sites integrated with cased method in enhancing students™ cultural competence. This research involved 28 students who joined in English Culture in ELT course. Data was collected with observation, questionnaires, and documentation. Data analysis was done with a descriptive analysis. Research results obtained from the students™ perception regarding the media appearance, material and benefit. The data showed the score 83 for the appearance, 83 for the material presentation and 85 for the benefit of google sites cultural based. Based on this data, the research shows that digital media on google sites (case based) on the English culture in ELT is feasible to enhance students™ cultural competence.keywords: Cultural competence, Digital media, Google site, Case base